A unified definition of CRM towards the successful adoption and implementation - Rababah, Khalid; Mohd, Haslina; Ibrahim, Huda (2010)
Attempts to define Customer Relationship Management (CRM) have been varied and many,reflecting the diverse academic backgrounds of CRM scholars. The inexistence of a unified definition of CRM leads to undesired and unexpected outcomes from the adoption and implementation of CRM. Hence, this paper attempts to come out with a unified definition of CRM. Content-analysis is carried out to find out the main and most important facets of CRM definition from the existing literatures in the fields of marketing, management, and information system. From the content analysis, this paper proposes a unified definition of CRM. This definition could provide great help for researchers and practitioners in the field of CRM. In addition, this unified definition of CRM could enhance the successful adoption and implementation of CRM.